Peningkatan Hasil Belajar Biologi Siswa Melalui Penerapan Media Video Animasi Tiga Dimensi (3D) - Dharma Ferry; Jepriadi; Dairabi Kamil (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2019)
ABSTRACT: Three-dimensional (3D) animation video is one of the media that can be applicated by teachers in the learning process. The use of this media is an alternative for teachers as an effort to improve the learning quality, especially in biology subjects. This study aims to determine the increase in student biology learning outcomes through the application of three-dimensional (3D) animation video media. This research is a classroom action research conducted in two cycles. The research subjects consisted of the students of State Junior High School Number 19 of Kerinci. Data collection techniques through observation and test sheets. Based on the results of data analysis, the average post-test score obtained in the first cycle was 74,94 with the percentage of students achieving Minimum Mastery Criteria (KKM) was 55,5%. In the second cycle, the average post-test score was 81,27 with the percentage of students who reached the minimum mastery criteria (KKM) was 88,8%. The results showed that the application of three-dimensional (3D) animation video media influenced the improvement of student biology learning outcomes.Keywords: 3D Animation Video, Biology Learning Outcomes, Learning Media ABSTRAK: Media video animasi tiga dimensi (3D) adalah salah satu media yang dapat diaplikasikan guru dalam proses pembelajaran. Penggunakan media ini menjadi alternatif bagi guru sebagai usaha untuk meningkatkan kualitas pembelajaran, khususnya pada mata pelajaran biologi. Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar biologi siswa melalui penerapan media animasi tiga dimensi (3D). Penelitian ini adalah penelitian tindakan kelas yang dilakukan dalam dua siklus. Subyek penelitian terdiri dari siswa SMP Negeri 19 Kerinci. Teknik pengumpulan data melalui lembar observasi dan tes. Berdasarkan hasil analisis data, diperoleh rata-rata nilai post-test pada siklus pertama adalah 74,94 dengan persentase siswa yang mencapai Kriteria Ketuntasan Minimum (KKM) sebesar 55,5% . Pada siklus kedua diperoleh rata-rata nilai post-test adalah 81,27 dengan persentase siswa yang mencapai Kriteria Ketuntasan Minimum (KKM) sebesar 88,8%. Hasil penelitian menunjukkan bahwa penerapan media video animasi tiga dimensi (3D) berpengaruh terhadap peningkatan hasil belajar biologi siswa.Kata Kunci: Video Animasi 3D, Hasil Belajar Biologi, Media Pembelajaran